Identification of monosomy 3 in choroidal melanoma by chromosome in situ hybridisation. Issue 12 (17th November 2004) - Sandinha, M T; Farquharson, M A; Roberts, F
Abstract : Background/aims: In uveal melanoma monosomy 3 is emerging as a significant indicator of a poor prognosis. To date most cytogenetic studies of uveal melanoma have utilised fresh tissue or DNA extracted from tissue sections. In this study chromosome in situ hybridisation (CISH) was used to study monosomy 3 in tissue sections. The copy number of chromosome 3 was determined and related to patient survival. Methods: Archival glutaraldehyde or formalin fixed, paraffin embedded material was obtained from 30 metastasising and 26 non-metastasising choroidal melanomas. Hybridisations were performed using centromere specific probes to chromosomes 3 and 18. Chromosome 18 was included as a control as previous abnormalities in uveal melanoma have not been described. Chromosomal imbalance was defined on the basis of changes in both chromosome index and signal distribution. Results: CISH was successfully performed on both glutaraldehyde and formalin fixed tissue. Four cases were unsuccessful because of extensive tumour necrosis. All cases were balanced for chromosome 18. Monosomy 3 was detected in 15 of the 26 cases of metastasising melanoma; the 26 non-metastasising tumours were all balanced for chromosome 3. Monosomy 3 was significantly associated with metastases related death. Conclusion: CISH can successfully identify monosomy 3 in archival glutaraldehyde or formalin fixed, paraffin embedded tissue sections. Similar to previous studies monosomy 3 is a significant predictor of metastases related death.